2018
DOI: 10.1386/cjmc.9.2.205_1
|View full text |Cite
|
Sign up to set email alerts
|

The role of shared ethnicity in facilitating stepwise migration of educated and skilled individuals: The case of Iranian graduate students in Turkey

Abstract: In this article, we examine the status of Iranian graduate students as stepwise global skilled migrants who enrol at Turkish universities, but with the intention of moving to their final destination country in the West. Based on survey data we analyse their migration strategies and career plans at mezzo-level, and conclude that more than 72 per cent of respondents can indeed be classified as stepwise migrants. First, Turkey is a preferred intermediate country particularly for migration of Iranian graduate stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Most participants were between 26 and 30 years old, and 63% of the sample were Iranian students of Azerbaijani ethnic background, whereas the rest were of Persian ethnicity. Although it is not possible to retrieve statistics on the ethnic background of Iranian students in Turkey, anecdotal evidence and other research (Sadri & Chaichian, 2018) suggests that, in terms of ethnicity, participants were fairly representative for Iranian students in Turkey at that time.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most participants were between 26 and 30 years old, and 63% of the sample were Iranian students of Azerbaijani ethnic background, whereas the rest were of Persian ethnicity. Although it is not possible to retrieve statistics on the ethnic background of Iranian students in Turkey, anecdotal evidence and other research (Sadri & Chaichian, 2018) suggests that, in terms of ethnicity, participants were fairly representative for Iranian students in Turkey at that time.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that there have not been any systematic studies of this phenomenon. And, for example, although Sadri and Chaichian (2018) found that 72% of graduate Iranian students intended to migrate stepwise from Turkey, they did not ascertain whether these students migrated in the end.…”
Section: Iranian Students Going Abroadmentioning
confidence: 99%
See 3 more Smart Citations